Interpretation Phraseological Units Denoting Cultural Identity (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is devoted to the ethnocultural interpretation of phraseological units formed on the basis of the ethnocultural views of the people in both Uzbek and English. The article demonstrates through examples that phraseological units serve both as a source of information about a people’s culture and as a vivid linguistic expression of national-cultural linguistic identity.a